Jenis, Strategi, dan Fungsi Tindak Tutur dalam Wawancara oleh Tokoh yang Sedang Menjadi Pusat Perhatian Publik - Rosendra, Nayatri Putri; Manaf, Ngusman Abdul (Universitas Negeri Padang, 2024)
This study aims to identify and describe the types, strategies, and functions of speech acts in interviews conducted with public figures who are currently in the spotlight. This research is descriptive in nature, employing both qualitative and quantitative approaches. The data consists of utterances from three prominent figures who are currently the focus of public attention. The source of the data is interview videos from the